An approach to modeling blast and fragment risks from improvised explosive devices - Oubay Hassan (Applied Mathematical Modelling, 2017)
In this paper, we develop numerical methods for modeling blast and fragments generated from explosive detonation and apply them to scenarios representing improvised explosive devices in confined spaces. The detonation of condensed phase explosives is modeled with a programmed burn method in a three-dimensional multimaterial flow solver. This solver has been coupled with a Lagrangian particle solver to model the acceleration of explosive-driven fragments. We first simulate an explosion in a long cylindrical tube to validate the fluid solver for a partially-confined blast. We then simulate explosions on a subway train platform for 10 kg and 30 kg C4 charges. The maximum shock overpressure and impulse are used to predict the risk of common blast injuries. To represent improvised explosive threats, we model C4 charges with spherical, cylindrical, and disk shapes that are surrounded by a layer of spherical fragments. We find that the explosive charge shape plays an important role in the acceleration of the spherical fragments. Finally, a realistic scenario of an improvised explosive detonation near a bomb technician is investigated to assess fragment trajectory and blast loads in the near field.